Changes in Pool Sizes of Free Amino Acids and Amides in Leaves and Plastids of Zea mays during Leaf Development - Chapman, David J. (1979)
The concentrations of free amino acids and amides within isolated maize (Zea mays L.) plastids were determined and compared with concentrations in the leaf tissue. The concentrations were different for each individual amino acid and varied between 1 and 10 millimolar. At five different developmental stages concentrations in the plastids were greater than those in the intact leaf tissue. During development, from the proplastid stage to the mature chloroplast, the amount of each amino acid per plastid remained relatively constant, but there were decreases in concentrations of plastid amino acids resulting from the developmental increase in plastid volume. In proplastids, the free amino acids were present in greater concentrations than those previously found to inhibit partially amino acid-synthesizing enzymes located in chloroplasts. In the chloroplasts, the molarities of the free amino acids were within the range known to inhibit amino acid-synthesizing enzymes.